Case Report: Recurrence of Positive SARS-CoV-2 Results in Patients Recovered From COVID-19 - Zhang, Ren-zi; Deng, Wang; He, Jing; Song, Yu-yan; Qian, Chun-fang; Yu, Qian; Wang, Dao-xin (Frontiers in Medicine, 2020)
Background: Coronavirus disease 2019 (COVID-19) is spreading throughout the world. Limited data are available for recurrent positive tests for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by nucleic acid detection in patients with long disease duration. Methods: We report four cases of COVID-19 with recurrently positive for SARS-CoV-2 during the disease progression. Results: Our data indicate that patients recovered from COVID-19 showed recurrently positive for SARS-CoV-2 by nucleic acid detection with no symptoms and normal chest CT,. Conclusions: The dynamic surveillance of SARS-CoV-2 by nucleic acid detection and serological assays is important for asymptomatic patients who might be potentially infectious.